2020
DOI: 10.1038/s41598-020-61096-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Hidden Details of Nanostructure in a Pharmaceutical Cream

Abstract: Creams are multi-component semi-solid emulsions that find widespread utility across a wide range of pharmaceutical, cosmetic, and personal care products, and they also feature prominently in veterinary preparations and processed foodstuffs. The internal architectures of these systems, however, have to date been inferred largely through macroscopic and/or indirect experimental observations and so they are not well-characterized at the molecular level. Moreover, while their long-term stability and shelflife, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…In the studies reported here, we extend our investigations on model creams [ 3 , 12 ], investigating formulations based around the UK licensed, British Pharmacopoeial product, Aqueous Cream B.P. In keeping with Eccleston’s studies [ 11 , 16 ], we explore the consequences of changing the added co-surfactant on the molecular structure, rheology and stability of the creams and their corresponding ternary systems and elucidate the role of the co-surfactant alcohols in the gel network formation.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…In the studies reported here, we extend our investigations on model creams [ 3 , 12 ], investigating formulations based around the UK licensed, British Pharmacopoeial product, Aqueous Cream B.P. In keeping with Eccleston’s studies [ 11 , 16 ], we explore the consequences of changing the added co-surfactant on the molecular structure, rheology and stability of the creams and their corresponding ternary systems and elucidate the role of the co-surfactant alcohols in the gel network formation.…”
Section: Introductionmentioning
confidence: 55%
“…SANS measurements were made on one-day-old creams and their corresponding ternary systems as presented in Table 1 , with all samples prepared with all components protiated in D 2 O. Samples were loaded in purpose-built cells as reported previously [ 3 ] and measurements were made on the LoQ instrument at the ISIS pulsed neutron source (STFC Rutherford-Appleton Laboratory, Harwell Oxford, United Kingdom). For each sample, the SANS measurements were recorded at 298, 305, 310 and 318 K (± 0.1 K) with the sample environment temperature controlled using a Julabo water bath [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations